2020
DOI: 10.31234/osf.io/kf29y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

I'm Simply the Best, Better than All the Rest - Narcissistic Leaders and Corporate Fundraising Success

Abstract: We examine the relationship between leader grandiose narcissism, composed of admiration and rivalry, and corporate fundraising success in a sample of 2377 organizational leaders. To examine a large sample of leaders, we applied a machine-learning algorithm to predict leaders' personality scores based on leaders' Twitter profiles. We found that admiration was positively related to - while rivalry was negatively related to corporate fundraising success (in '000s). Analyses also showed that leader gender does not… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Hence, we measure and control for all Big Five leader and follower personality traits. Previous work [e.g., [36][37][38][39] has shown that personality traits can be measured accurately and successfully in online contexts using social media data. Therefore, in our third step, each Twitter profile was fed into the IBM Watson Personality Insights PLOS ONE API, which extracts and analyzes social media textual data to identify personality traits based on linguistic analysis [40].…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Hence, we measure and control for all Big Five leader and follower personality traits. Previous work [e.g., [36][37][38][39] has shown that personality traits can be measured accurately and successfully in online contexts using social media data. Therefore, in our third step, each Twitter profile was fed into the IBM Watson Personality Insights PLOS ONE API, which extracts and analyzes social media textual data to identify personality traits based on linguistic analysis [40].…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Linguistic-based text analytics or linguistic analytics exploits information about the syntax and semantics of a language as well as lexicons, to extract important information from textual data. For instance, while Gruda et al (2020) , Gruda, Karanatsiou, Mendhekar, Golbeck, & Vakali, (2021) , Gruda, Karanatsiou, Hanges, Goldbeck, & Vakali, (2021) , and Karanatsiou et al (2020) applied linguistic-based text analytics on Twitter data to detect traits such as narcissism and attachment, Ojo and Rizun (2019) employed linguistic markers found in negative free-text comments provided by hospital service users to determine the frequency and intensity of the associated negative experience. In addition, more recent work by Gruda and Ojo (2021) and Gruda, Ojo & Psychogios (2021) have also demonstrated that mental health signals can be identified from publicly available Twitter data.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Is personality/crowdfunding a core concept of the paper or just used as an example to research a related topic? For example, we excluded Gruda et al ( 2021 ) as crowdfunding is just a concept to which the paper's results are compared (i.e. “We discuss and compare our findings to previous work on narcissism and crowdfunding.” (Gruda et al 2021 , p. 1)); another example is the exclusion of Wang et al ( 2017 ) who investigate sentiments rather than personality (“The study proves that positive sentiment in the blurb and detailed description promotes the successful campaigns” (Wang et al, 2017 , p. 2)).…”
Section: Methodsmentioning
confidence: 99%